Biology, Ecology, and Management of Rednecked Peanutworm (Lepidoptera: Gelechiidae). (22nd June 2020) - Pinto, J R L; Boiça, A L; Fernandes, O A
Abstract: The rednecked peanutworm, Stegasta bosqueella (Chambers), is the main lepidopteran pest in South and Central American peanut fields. The species name was misspelled earlier in the literature and the incorrect name is still more cited. In this review, we revisit the history of S. bosqueella classification. Although the rednecked peanutworm is an important defoliator in some peanut producing countries, there is scarce information on some aspects of the biology as well as plant response to this insect species. Economic threshold levels are not yet well established and, consequently, decision making is compromised. Chemical control is the main tool used to control larval infestations. Moreover, some studies on host plant resistance, biological control, and attract-and-kill strategy were conducted to control the rednecked peanutworm. These tactics were promising and could be useful to enhance a peanut integrated pest management program. We present here a review of S. bosqueella life history, biology, ecology, and management options as well as needs for enhancing the current control strategies.